Looking at textiles : a guide to technical terms - Phipps, Elena (Los Angeles, Calif. : J. Paul Getty Museum, 2011)
A guide to the fundamentals of the materials and techniques used to create textiles.
Includes bibliographical references and index.
Keywords: Textile fabrics -- Terminology; Textile fabrics -- Terminology